Where do KIBS workers work in Germany? Shifting patterns of KIBS employment in metropoles, regiopoles and industrialised hinterlands - Growe, Anna (ERDKUNDE, 2016)
In the years following reunification, the polycentric German urban system has undergone changes as regards the location of employees in knowledge-intensive business service (KIBS) professions. For the purposes of analysing functional spatial patterns, those spatial patterns exhibiting above-average increases or decreases in the numbers of employees within KIBS professions were identified on the basis of employment data. Correlations in the spatial affinities within service professions of differing compositions were mapped, leading to the identification of four patterns. Based on these patterns, spatial differentiation arising between the various services in the German urban system has been interpreted as functional specialisation. The basis of functional specialisation, with reference to the concept of knowledge bases, is differentiation into the following three service industries: technological services, consulting services and creative services.